2022
DOI: 10.1021/acsami.2c00263
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Aging Properties of Ag-, Ag/Cu-, and Ag Cluster-Doped Amorphous Carbon Coatings Produced by Magnetron Sputtering for Space Applications

Abstract: Inside a spacecraft, the temperature and humidity, suitable for the human crew onboard, also creates an ideal breeding environment for the proliferation of bacteria and fungi; this can present a hazard to human health and create issues for the safe running of equipment. To address this issue, wear-resistant antimicrobial thin films prepared by magnetron sputtering were developed, with the aim to coat key internal components within spacecrafts. Silver and copper are among the most studied active bactericidal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…The hardness and elastic modulus of MAC were experimentally reported to be proportional to the fraction of sp 3 orbitals, and it was proved by MD simulation (Figures 5c). [15,86] Since metalloid or metal doping (Si, [58,63] B 4 C, [54] Ag, [87,88] Cu, [87] Ti [59,60] ) in the a-C thin film significantly increased the hardness, the depth of indentation after the friction scratch test was much less in the Ti (9.75%)-doped a-C thin film. However, surface cracks and wear scars were prominent because the enhanced hardness lost the plasticity of the pristine a-C thin film.…”
Section: Properties Of the A-c Thin Filmsmentioning
confidence: 99%
“…The hardness and elastic modulus of MAC were experimentally reported to be proportional to the fraction of sp 3 orbitals, and it was proved by MD simulation (Figures 5c). [15,86] Since metalloid or metal doping (Si, [58,63] B 4 C, [54] Ag, [87,88] Cu, [87] Ti [59,60] ) in the a-C thin film significantly increased the hardness, the depth of indentation after the friction scratch test was much less in the Ti (9.75%)-doped a-C thin film. However, surface cracks and wear scars were prominent because the enhanced hardness lost the plasticity of the pristine a-C thin film.…”
Section: Properties Of the A-c Thin Filmsmentioning
confidence: 99%
“…Recent studies on Ag and Cu NPs have shown that there is a strong influence of metal particle size, shape, surface charge, and other factors on the release of metal ions that are critical to bactericidal and virucidal properties. Smaller metal NPs oxidize more easily, releasing more metal ions which in turn increases the bactericidal effect [5]. Cu is less expensive than Ag, but it is also a very practical choice because it possesses not only bactericidal but also virucidal properties at the same time and can serve as a multifunctional protecting coating [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various approaches explored, the utilization of novel materials with inherent antibacterial properties has shown great promise. It has been shown that silver, copper, and their compounds are among the most popular materials used for different antimicrobial and biomedicine applications 5, 6 because of their high bactericidal performance 7 . It should be noted that Cu has been recognized by the United States Environmental Protection Agency (EPA) as the first metallic antimicrobial agent in 2008 but with ongoing waterborne hospital-acquired infections and antibiotic resistance, research on Cu as an antimicrobial agent is booming again 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various approaches such as spray deposition, spin-coating, sol–gel, acid etching, anodic oxidation, physical vapor deposition (PVD), and electrodeposition have been employed to modify antibacterial surfaces, and alter their surface properties, and topology 55 . Among these methods, magnetron sputtering has been shown in several studies to be a suitable and feasible way to modify antibacterial coatings 56 58 . This method offers an excellent opportunity to produce homogeneous, smooth, and dense coatings with a rapid deposition rate, thereby increasing the coating-substrate adherence 59 , 60 .…”
Section: Introductionmentioning
confidence: 99%